Abundance Trends in Papilionid Butterflies over a Decade: Implications and Conservation Lessons for Butterflies in Kerala, India - Anto, Ignatious; Anto, Mary (Indian Forester, 2017)
Changes in abundance of butterfly species across temporal scales is an area in ecological research which has hardly been investigated in the Indian context. In this study, we have attempted to analyse the butterfly count data recorded at the Kerala Forest Research Institute, Peechi, India. Correlations between the weather parameters and the butterfly abundance were sought and the species relation to these variables were analysed. Correlation between the species and weather variables in the first round of sampling was tested against the second round of sampling conducted after a gap of ten years. Finally, linear regression was performed to ascertain the relationship between the variables. The results of this study indicate that identifying patterns of change in the abundance of butterfly species in response to abiotic factors is crucial to understanding the complex nature of butterfly communities.